Effect of calcium chloride extracted from eggshell in maintaining quality of selected freshâcut fruits - Rohit J. Thakur; Hamad Shaikh; Yogesh Gat; Roji B. Waghmare (International Journal of Recycling of Organic Waste in Agriculture)
Purpose A study was conducted to extract calcium chloride from eggshell and also to check the effect of commercially available and extracted calcium chloride on quality characteristics of fresh-cut fruits. Method Eggshells were mixed with a hydrochloric acid solution and stirred occasionally until no gas bubbles were observed (3 h). The mixture was centrifuged at 3500 rpm for10 min at 4 °C, the supernatant was separated and heated to 110â115 °C until dried, this yielded calcium chloride crystals or eggshell calcium chloride. The fresh-cut fruit cubes were separately dipped in a solution of 2% calcium chloride extracted from egg shell and 2% commercially available for 5 min. The cubes are packed in polypropylene plastic bags and stored at 5 °C. Analyses were done at 5-day intervals for a time period of 25 days. The microbial count, physical (firmness, weight loss and color), chemical (pH, titratable acidity, total soluble solids, DPPH, reducing sugar, total phenolic content, and ascorbic acid content), and sensory analysis were determined at regular interval throughout the storage period. Results Calcium chloride extracted from egg shell was capable to maintain shelf-life for 15 days, whereas commercial calcium chloride was able to maintain shelf-life for 20 days. This shows calcium treated fresh-cut fruits have an improved and enhanced shelf-life than control (non-treated samples). Conclusion The study proved that dipping fresh cut fruits in CaCl2 solution (extracted from eggshell and commercially available) extend its shelf-life for 15 days.